Prophet Muhammad (PBUH): The Savvy Politician - Mohd Azmir Mohd Nizah; Muhammad Mustaqim Mohd.Zarif; Paimah Atoma; Hisham Muhammad Taky Eldin Kandil (Universiti Sains Islam Malaysia, 2024)
This paper is a preliminary study on the concept of Islamic creative thinking through the life of Prophet Muhammad (pbuh). This study is aimed to reassess the creativity of Prophet Muhammad (pbuh) specially in political and statesmen point of view. This study also aimed to highlight his creativity in diplomacy, conflict resolution and international affairs. The study employed qualitative method with content analysis approach by evaluating on necessary and relevant reports, articles and texts. It is hoped that this preliminary paper will provide a distinctive perspective on the concept of creativity and innovation and its necessity in contemporary Islamic political approach which should be considered as an important characteristics for both modern Islamic and western worlds.